HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA KELAS XI IPA 1 SMA NEGERI 1 TAPUNG HULU SELAMA PANDEMI COVID-19 - Manalu, Aldo Jesandro; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the relationship between learning motivation and learning outcomes for Physical Education, Sports and Health, for class XI IPA 1 SMA Negeri 1 Tapung Hulu during the Covid-19 pandemic. The sample in this study was 34 students of class XI IPA 1 SMA Negeri 1 Tapung Hulu. The results of the study of the relationship between learning motivation and learning outcomes of physical education, sports and health of class XI IPA 1 SMA Negeri 1 Tapung Hulu during the Covid-19 pandemic together there was a significant relationship. This can be seen with a significant value of 0.683 > 0.339 at the significant level (5%). This shows that the value of the relationship between learning motivation and learning outcomes for physical education, sports and health of class XI IPA 1 SMA Negeri 1 Tapung Hulu during the Covid-19 pandemic is at the level of a "strong" relationship. Thus it can be concluded that students who have high learning motivation have a greater chance of obtaining better learning achievement than students who have low learning motivation.Key Words: Learning Motivation, Learning Outcomes, Covid 19 Pandemic